Assessment of Harmonic Distortion in School Buildings Equipped with Grid-Connected PV Systems - Pranjić, Franjo (Journal of Energy Technology, 2025)
The integration of photovoltaic systems into power grids can impact power quality, particularly concerning voltage and current harmonics. This study investigates the power quality of a photovoltaic system integrated into the electrical system of an educational facility, focusing on harmonic distortion in both voltage and current. Comprehensive measurements were conducted across three phases and analysed according to the EN 50160 and IEEE 519 Standards. The results demonstrated that, while the voltage quality meets EN 50160 requirements consistently, indicating stable voltage levels, the current measurements revealed significant harmonic distortion. Notably, Phase 2 exhibited Total Harmonic Distortion values substantially above the acceptable limits, with Phase 1 and Phase 3 also showing elevated Total Harmonic Distortion. To address these issues, the study recommends the implementation of advanced harmonic filters and optimisation of inverter technologies. These measures are crucial for enhancing power quality, and ensuring compliance with the industry Standards in high photovoltaic penetration scenarios.